Dinuclear iridium and rhodium complexes with bridging arylimidazolide-N3, C2 ligands: synthetic, structural, reactivity, electrochemical and spectroscopic studies. Issue 39 (30th July 2015) - He, Fan; Ruhlmann, Laurent; Gisselbrecht, Jean-Paul; Choua, Sylvie; Orio, Maylis; Wesolek, Marcel; Danopoulos, Andreas A.; Braunstein, Pierre
Abstract : In doubly C, N-bridged dinuclear complexes with 1-arylimidazolide ligands, the Ir head-to-head isomer can be thermally converted to the head-to-tail isomer. Abstract : Deprotonation of 1-arylimidazoles (aryl = mesityl (Mes), 2, 6-diisopropylphenyl (Dipp)), with n -butyl lithium afforded the corresponding derivatives (1-aryl-1 H -imidazol-2-yl)lithium (1a, Ar = Mes;1b, Ar = Dipp) in good yield. Reaction of1a with 0.5 equiv. of [Ir(cod)(μ-Cl)]2 yielded two geometrical isomers of a doubly C2, N3-bridged dinuclear complex [Ir(cod){μ-C3 H2 N2 (Mes)-κC2, κN3}]2 (3 ), 3H–H, a head-to-head (H–H) isomer of C S symmetry, and3H–T, the thermodynamically preferred head-to-tail (H–T) isomer of C 2 symmetry. The metallated carbon of the 4 electron donor anionic bridging ligands has some carbene character, reminiscent of the situation in N-metallated protic NHC complexes. Displacement of cod ligands from3H–H and3H–T afforded the tetracarbonyl complexes [Ir(CO)2 {μ-C3 H2 N2 (Mes)-κC2, κN3}]2 4H–H and4H–T, respectively. The reaction with PMe3, which gave only one complex, [Ir(CO)(PMe3 ){μ-C3 H2 N2 (Mes)-κC2, κN3}]2 (5 ), demonstrates that the isomerization of the central core Ir[μ-C3 H2 N2 (Mes)-κC2, κN3]2 Ir from H–H to H–T on going from4H–H to5 is readily triggered by phosphine substitution under mild conditions. Oxidative-addition of MeI to5 afforded the formally metal–metal bonded d 7 –d 7 complex [Ir2 (CO)2 (PMe3 )2 (Me)I{μ-C3 H2 N2 (Mes)-κC2, κN3}2 ] (6 ). The blue [Ir(C2 H4 )2 {μ-C3 H2 N2 (Mes)-κC2, κN3}]2 (7 ) and purple [Rh(C2 H4 )2 {μ-C3 H2 N2 (Dipp)-κC2, κN3}]2 (9 ) tetraethylene complexes were also obtained with only a H–T arrangement of the bridging ligands. Although only modestly efficient in alkane dehydrogenation, complex7 was found to be a more active pre-catalyst than3H–T, 4H–T and5, probably because of the favorable lability of the ethylene ligands. From cyclic voltammetry, exhaustive coulometry and spectroelectrochemistry studies, it was concluded that3H–T undergoes a metal-based one electron oxidation to generate the mixed-valent Ir(i )/Ir(ii ) system. The energy of the intervalence band for the orange dirhodium complex [Rh(cod){μ-C3 H2 N2 (Mes)-κC2, κN3}]2 (8 ) is shifted toward lower energies in comparison with3H–T, reflecting the decrease of the energy with the intermetallic distance. It was concluded from the EPR study that the Ir and Rh centres contribute substantially to the experimental magnetic anisotropy and thus to the singly occupied molecular orbital (SOMO) in the mixed-valent Ir(i )/Ir(ii ) and Rh(i )/Rh(ii ) systems. The molecular structures of3H–H, 3H–T, 8 and9 have been determined by X-ray diffraction.